PENGGUNAAN MEDIA PAKAN KACANG-KACANGAN TERHADAP POPULASI Corcyra cephalonica (Lepidoptera:Pyralidae) - Yocindi Roba; Jimmy Rimbing; James B. Kaligis (COCOS, 2019)
ABSTRACT Beanshave been known as a complementary source of protein with whole grains, such as rice and wheat. As the age of agricultural commodities grows there are serious problems that have been found, namely pests of diseases in agricultural crops. Disease pest attacks not only during growing process, but also after harvest. One of the warehouse pests that cause damage to the food commodity that is stored is Corcyra cephalonica. The aim of this research is to know the development of C.cephalonica population of Beans. The study was conducted at the Plant Pest and Disease Laboratory from March to July 2017. The observations were made after the eggs hatched and become imago. It has been counted every day of the population from C.cephalonica until it finished which is about 11 days of observation. The results showed that the red bean flour medium had the lowest average imago C. cephalonica population which is 7.28 individuals followed by green bean flour medium that was 8.36 individuals on average. Then on soybean flour media that is 9.52 individuals and on the highest peanut flour media is 9.8 individuals. Keywords : Beans, C. cephalonica